Strategi Pengembangan Usaha dalam Meningkatkan Jangkauan Pasar pada UMKM Bandeng Sultan di Kota Makassar - Luthfia Luthfia; Muhamma Ridwan; Wahyuni Zam (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
The fisheries sector plays a vital role in the national economy and represents a significant potential source of foreign exchange. The development of this sector must be strategically designed to address future challenges, which include anticipating changes in both production and consumer systems (markets), as well as shifts in resource potential. This study aims to identify and analyze effective business development strategies for UMKM Bandeng Sultan to expand its market reach. The research methodology includes both primary and secondary data collection through interviews and field observations, analyzed qualitatively using a descriptive approach. Data were collected directly from interviews and on-site observations to gain relevant insights into the current conditions of the Bandeng Sultan business. The results indicate that the SWOT coordinate score (0.6: 0.57) places the business in a favorable position, supporting the adoption of an aggressive growth strategy. Recommended strategic actions include enhancing digital and e-commerce marketing, expanding into the Java market and exploring export opportunities, diversifying product offerings and innovating flavor varieties, as well as improving product quality and hygiene standards. These findings demonstrate that UMKM Bandeng Sultan possesses strong internal capabilities and promising external opportunities for growth. Therefore, the implementation of aggressive strategies was considered appropriate to increase competitiveness and ensure long-term business sustainability in a highly competitive market environment.